Digging, damming or diverting?: small-scale irrigation in the Blue Nile Basin, Ethiopia - Eguavoen, I.; Derib, S.D.; Deneke, T.T.; McCartney, Matthew P.; Otto, B. A.; Billa, S.S. (2012)
The diversity of small-scale irrigation in the Ethiopian Blue Nile basin comprises small dams, wells, ponds and river diversion. The diversity of irrigation infrastructure is partly a consequence of the topographic heterogeneity of the Fogera plains. Despite similar social-political conditions and the same administrative framework, irrigation facilities are established, used and managed differently, ranging from informal arrangements of households and 'water fathers' to water user associations, as well as from open access to irrigation schedules. Fogera belongs to Ethiopian landscapes that will soon transform as a consequence of large dams and huge irrigation schemes. Property rights to land and water are negotiated among a variety of old and new actors. This study, based on ethnographic, hydrological and survey data, synthesises four case studies to analyse the current state of small-scale irrigation. It argues that all water storage options have not only certain comparative advantages but also social constraints, and supports a policy of extending water storage 'systems' that combine and build on complementarities of different storage types instead of fully replacing diversity by large dams.